E-Government Vs Kesiapan Birokrasi: Analisis Hambatan Teknis Dan Resistensi Kultural Dalam Digitalisasi Layanan Publik Di Kota Manado - ZUCI RAHMANI ZAINAL; ANGGITA CHAIRIAH; MADINATUL MUNAWWARAH RIDWAN; LULU QURRATA A'YUN (Universitas Mbojo Bima, 2026)
Abstract. The implementation of E-Government often encounters structural clashes between advanced digital systems and deep-seated bureaucratic readiness. This study aims to analyze the technical barriers and cultural resistance confronting the Manado City Government in implementing digitalized public services, such as the Manado Smart City ecosystem and electronic licensing applications. Using a descriptive qualitative approach, primary data was collected through in-depth interviews with structural officials, IT technicians, and public users, alongside secondary administrative records. The collected data was processed through interactive qualitative evaluation and systematic SWOT matrix modeling. The results demonstrate that while technical infrastructure deficits remain a challenge, cultural resistance—manifested as senior staff inertia, rigid hierarchical mindsets, and low digital efficacy—presents a deeper impediment to institutional agility. This paper provides concrete strategic recommendations, prioritizing adaptive digital culture cultivation, structural literacy mapping, and the deployment of a single unified application gateway to elevate regional public service performance.